Repurposing trazodone for Alzheimer’s disease to modulate soluble ST2 levels and alleviate Alzheimer’s pathology - Daniel Y. K. Wong; Wing-Yu Fu; Hyebin Uhm; Yuanbing Jiang; Yuki C. C. Yip; Vincent C. T. Mok; Timothy C. Y. Kwok; Li Ouyang; Amy K. Y. Fu; Nancy Y. Ip (Proceedings of the National Academy of Sciences, 2026)
Alzheimer’s disease (AD) is a multifactorial disorder involving various pathological mechanisms, such as amyloidosis, immune dysfunctions, and synaptic impairments, which are important therapeutic targets. Repurposing drugs to target these mechanisms offers a promising approach to reduce the costs and duration of drug development. Genetic studies underscore the critical role of microglial clearance of amyloid-beta (Aβ) in AD pathogenesis. Specifically, soluble ST2 (sST2)—one of the two major isoforms of the ST2 protein encoded by the IL1RL1 (interleukin-1 receptor-like 1) gene—acts as a decoy receptor isoform that interferes with IL-33/ST2 signaling and has been identified as a disease-modifying factor that impairs microglial Aβ clearance functions. In this study, we investigated drug repurposing opportunities to modulate sST2 levels and alleviate AD pathologies. Unbiased screening of commonly used medications in AD patients, followed by validation in model systems, identified trazodone—an antidepressant used to treat major depressive disorder—as a leading negative regulator of sST2. Trazodone primarily suppresses sST2 expression through its antagonistic effects on adrenergic signaling. In the APP/PS1 transgenic mouse model of AD, trazodone treatment enhanced microglial interaction with Aβ and alleviated Aβ pathology. Furthermore, trazodone reduced neurodegeneration and rescued synaptic deficits in APP/PS1 mice. Comprehensive molecular profiling of APP/PS1 mouse brains showed that trazodone restored the expression of synaptic proteins critical for synaptic integrity and plasticity. Overall, these findings demonstrate that trazodone is a promising repurposing candidate for AD that targets underlying immune dysfunctions and synaptic impairment.